Rancangan Pembuatan Aplikasi Indeks Beranotasi Surat Kabar Subjek Minangkabau Berbasis Web di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Yulesti, Fioni; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractÂ This article is about making of design application annotated index of the newspaper subject Minangkabau base on website in The Archives and Libraries of West Sumatera. The purpose of this article are: (1 making of design application annotated index of the newspaper subject Minangkabau base on website in The Archives and Libraries of West Sumatera; and (2) using of design application annotated index of the newspaper subject Minangkabau base on website in The Archives and Libraries of West Sumatera. The data is collected by direct observation to the newspaper. The example of this product is taken in Archieves and Library of West Sumatera. Base on the result the conclutions are. First, making of design application annotated index of the newspaper subject Minangkabau base on website in The Archives and Libraries of West Sumatera base on website in The Archives and Libraries of West Sumatera started with make the database at MySQL that use phpMyAdmin. The next step is connected the database with web application used sublime text 3. After that design the display of admin and user with different facilities. The admin display has facilities management data such as added data, deleted data, edited data, showed data, and searched data. The user display just has searched information dat. It aims to keep the data. Second, using of design application annotated index of the newspaper subject Minangkabau base on website in The Archives and Libraries of West Sumatera in The Archives and Libraries of West Sumatera may use with some method, that is: (1) direct search information by viewing the display information data; (2) typing keyword that user know in the search field; (3) searching information based on the form of the newspaper like article, opinion, and news; and (4) searching information based on the sort of the title, author name (article and opinion), date, and keyword. Keywords: indexing, annotated, and website